Optimizing the pipeline of multipurpose prevention technologies: opportunities across women's reproductive lifespans - Bershteyn, Anna; Resar, Danielle; Kim, Hae-Young; Platais, Ingrida; Mullick, Saiqa (Frontiers in Reproductive Health, 2023)
HIV/AIDS and maternal mortality are the two leading causes of death among women of reproductive age in sub-Saharan Africa. A growing body of research investigates opportunities for multipurpose prevention technologies (MPTs) that prevent unintended pregnancy, HIV, and/or other sexually transmitted infections (STIs) with a single product. More than two dozen MPTs are currently in development, most of them combining contraception with HIV pre-exposure prophylaxis, with or without protection from other STIs. If successful, such MPTs could offer women benefits at multiple levels: greater motivation for effective use; lower product administration burden; accelerated integration of HIV, STI, and reproductive health services; and opportunities to circumvent stigma by using contraception as a “fig leaf” for HIV and/or STI prevention. However, even if women find respite from product burden, lack of motivation, and/or stigma in contraceptive-containing MPTs, their use of MPTs will be interrupted, often multiple times, over the reproductive lifecourse due to desire for pregnancy, pregnancy and breastfeeding, menopause, and changes in risk. Interruptions to the benefits of MPTs could be avoided by combining HIV/STI prevention with other life-stage-appropriate reproductive health products. New product concepts could include combining prenatal supplements with HIV and STI prevention, emergency contraception with HIV post-exposure prophylaxis, or hormone replacement therapies for menopause with HIV and STI prevention. Research is needed to optimize the MPT pipeline based on the populations underserved by available options and the capacity of resource-constrained health systems to deliver novel preventative healthcare products.